Comparative analysis of corporate income tax calculation payable using Law Number 36 of 2008 with Government Regulation No. 23 of 2018 at Uni Indonesia Public Company - Harmana, I Made Dwi (Tennessee Research International of Social Sciences, 2025)
Taxpayers often make mistakes in determining the tax burden payable which causes inefficiency and losses for taxpayers and the government. The purpose of this study is to determine the appropriate and profitable tax provisions for business entities in determining Income Tax Payable. The data obtained are sourced from the Profit and Loss Report of PT Uni Indonesia in 2022 and Gross Turnover in 2022. The analysis method used is a comparative descriptive analysis between the calculation of corporate income tax using Law No. 36 of 2008 and Government Regulation no. 23 of 2018. The results of this analysis study concluded that PT Uni Indonesia is more profitable by using Law No. 36 of 2008, because the tax burden owed is not there because after the fiscal correction PT Uni Indonesia experienced a fiscal loss and the loss can be compensated for the following year in a row for 5 years.